Patient-accessible online health records: Reconfigurations of clinical rhythms and doctors' front- and backstage spaces. (January 2022) - Petersson, Jesper; Backman, Christel
Abstract: With patients' increasing online access to medical information traditionally contained within healthcare institutions, researchers have argued that the spaces of medicine are increasingly becoming blurred, allowing patients to sidestep their doctors and challenge their prior information dominance. In this context, Sweden has recently been spotlighted as it allows its inhabitants to continually access medical record content online. Based on an interview study on Swedish doctors' clinical experiences of the patient-accessible online health record, this paper expands on the theme of emergent medical information spaces accessible to laypersons online by arguing that this not only may challenge the traditional spaces of medicine but can impose on its temporal orders too. We detail doctors' attitudes toward the patient-accessible online health record, patients as continually updated record readers, and how this may transform clinical work rhythms and affect doctors' perceptions of the boundary between front- and backstage spaces. We moreover show how doctors can avoid "inappropriate intrusion" into the record by delaying patient access, but also that doctors can experience patients opposing to adapt to doctors' preferred pace and instead attempting to control the clinical rhythm. By intertwining clinical rhythms with doctors' front- and backstage, this paper contributes with an extended analysis of the emergent spaces of online medical information, adding a temporal layer. The paper furthermore enlarges the existing sociological body on historical developments of medical records and adds a piece to the so-far piecemeal social science literature on how online records may affect the medical profession. Highlights: Providing patients' easy and swift access to record information online may impact doctors' clinical tempo. Patients accessing record information online can challenge doctors' boundaries between front- and backstage regions. Doctors may view patients swiftly accessing record information as being empowered, amending temporal information asymmetries. Doctors wish controlling patients' access to record information for professional reasons and to shield patients. Patients sometimes manage to access parts of the record doctors are yet unaware of.